American Journal of Community Psychology - Tebes, Jacob Kraemer; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The American Journal of Community Psychology publishes original quantitative, qualitative, and mixed methods research; theoretical papers; empirical reviews; reports of innovative community programs or policies; and first person accounts of stakeholders involved in research, programs, or policy. The journal encourages submissions of innovative multi-level research and interventions, and encourages international submissions. The journal also encourages the submission of manuscripts concerned with underrepresented populations and issues of human diversity. The American Journal of Community Psychology publishes research, theory, and descriptions of innovative interventions on a wide range of topics, including, but not limited to: individual, family, peer, and community mental health, physical health, and substance use; risk and protective factors for health and well being; educational, legal, and work environment processes, policies, and opportunities; social ecological approaches, including the interplay of individual family, peer, institutional, neighborhood, and community processes; social welfare, social justice, and human rights; social problems and social change; program, system, and policy evaluations; and, understanding people within their social, cultural, economic, geographic, and historical contexts. Contributions are welcome in such as areas as: the prevention of problems in living and the prevention of behavioral health disorders; the promotion of competence, resilience, well-being, and health; the design, implementation, and evaluation of community-based interventions; self- and mutual help; the empowerment of individuals, groups, and communities as well as historically disenfranchised groups; collective social action; oppression and human liberation; social network analysis and mobilization; advocacy and coalition-building; community organizing; organizational development, community development, and institutional development; consultation and technical assistance; community education; professional training; social change and systems reform; and community-based participatory research, collaborative research, and interdisciplinary research. The American Journal of Community Psychology is a publication of the Society for Community Research and Action: The Division of Community Psychology of the American Psychological Association.
Keywords: Public health; Clinical psychology; Health psychology; Personality; Social psychology; Community psychology; Environmental psychology; Community and Environmental Psychology; Personality and Social Psychology; Clinical Psychology; Health Psychology; Public Health